Pattern of antenatal care among antenatal clinic attendees at Alex Ekwueme Federal University Teaching Hospital Abakaliki, Nigeria - Oliobi, Wendy Chinwe; Nwafor, Johnbosco Ifunanya; Ikeotuonye, Arinze Chidiebere; Nweke, Nnenna Assumpta; Uche Nwidagu, Bridget Nkiruka; Okoye, Paschal Chijioke; Onyema, Malachy Chizoba (International Journal of Research in Medical Sciences, 2019)
Background: Antenatal care is a core component of safe motherhood initiative and it helps indirectly in reducing maternal and perinatal morbidity and mortality. Despite the obvious benefits of antenatal care, utilization of this service is very poor in our environment. Therefore, this study sought to assess the gestational age at booking, the reason for booking and determine the factors responsible for late booking among antenatal attendees at the Alex Ekwueme Federal University Teaching Hospital Abakaliki. Methods: This was a cross-sectional descriptive study conducted 5th May 2016 and 10th June 2016 among 258 consecutive pregnant women who presented for booking at the antenatal clinic of the hospital, using self-administered, pre-tested questionnaires. Statistical analysis was done using Epi Info 7.2.1. Results: The mean gestational age at booking was 21.5±4.8 weeks. The mean age of the respondents was 28.2±3.8 years while the mean parity was 1.5±1.6 years. Most of the women booked after the first trimester of pregnancy, only 61(24.8%) of the respondents booked in the first trimester of pregnancy. Majority of the women had no problem at booking 36.7%. Women aged 20-34 years booked late compared to women aged less than 20 years and those above 34 years and the difference was statistically significant. There was no statistically significant difference in maternal parity, education, marital status and religion with regards timing of booking. However, women who were sick during the first trimester were more likely to book early as well as women who booked early in their previous pregnancy. Conclusions: Late booking was common in our environment. There is an urgent need for increase awareness of the benefits of early booking to pregnancy outcome.